Unforeseen circumstances that alter substantially the agreed terms under construction contracts: a look at the effects of the Covid-19 pandemic - Valencia Cerasa, José Manuel (2020)
The institution of force majeure in regard with the Covid-19 pandemic is analyzed, emphasizing in a methodology to analysis and identify the affectation in deferred execution contracts, especially construction contracts. There is a firmly necessity to consider each one of the contractual duties and obligations, as well as the casuistically definition about a genuine unreached contract execution or only a greater difficulty of its accomplishment, examining in this last event the facts related to the agreed diligence standard. Under this last point of view, the article analyzes whether it is allowed for one of counterparts to exclude some part of contract´s object due to excessive onerousness or difficulty of supervening compliance. The pertinence of contract`s breach exception is matter of review, concluding that it`s not always forceable in case of non-satisfaction of proposed and agreed benefits by one of counterparts. The analysis focuses on Chilean regulation, without prejudice that it may be extrapolated to foreign legal scenarios. Also, an examination of the hardship clauses for supervening circumstances is carried out and its application to construction contracts is postulated.